2021
DOI: 10.1002/open.202100082
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Induced Emissive Luminogens for Sensing of Toxic Elements

Abstract: The major findings in the growing field of aggregation induced emissive (AIE) active materials for the detection of environmental toxic pollutants have been summarized and discussed in this Review article. Owing to the underlying photophysical phenomenon, fluorescent AIE active molecules show more impact on sensing applications. The major focus in current research efforts is on the development of AIE active materials such as TPE based organic fluorescent molecules, metal organic framework, and polymers that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…The probe has good practical applicability in the preparation of test strips and detection of Hg 2+ in a water sample [ 59 ]. Our group recently described different AIE active luminogens that are designed for selective and sensitive detection of various toxic metal ions [ 60 ]. Elemental copper plays a very important role in various physiological processes in the environment.…”
Section: Aggregation Induced Emission (Aie) Active Molecules For Sensing Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The probe has good practical applicability in the preparation of test strips and detection of Hg 2+ in a water sample [ 59 ]. Our group recently described different AIE active luminogens that are designed for selective and sensitive detection of various toxic metal ions [ 60 ]. Elemental copper plays a very important role in various physiological processes in the environment.…”
Section: Aggregation Induced Emission (Aie) Active Molecules For Sensing Applicationmentioning
confidence: 99%
“… A photograph representing the sensing performance of the probe towards CN − ion in an aqueous solution in the presence of other anions under: ( a ) visible light and ( b ) UV light (365 nm). Reprinted from reference [ 60 ] with the permission of the American Chemical Society. …”
Section: Figurementioning
confidence: 99%
“…Many ions are associated directly and indirectly with living organisms, but their excess may cause disturbances in the life cycle of the organisms. [1][2][3] Cyanide is considered to be one of the hazardous ions due to its toxicity 4 and strong binding to cytochrome P450. 5 Also, it is a serious threat to human beings due to its effects on the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…The AIE-active materials have been applied in ground-breaking applications, such as chemo/biosensors, hazardous detection, optoelectronic devices, therapeutics, theranostics and stimuli responsive imaging studies. [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. In particular, applications of AIE-active materials in opto-electronics, biosensors, imaging, therapeutic and theranostics are not only in great demand but also make a social impact [ 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the AIE of pyrene-based small molecules can be utilized for in vivo/in vitro imaging applications [ 35 ]. There are already many reviews on the aggregation-induced emission of several reported molecules in optoelectronic, bioimaging and theranostics [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. However, reviews on the pyrene-based AIE-active materials for bioimaging and theranostics applications are not readily available and will be delivered in this article (Note: considering the journal scopes, other optoelectronic applications of the AIE-active pyrene-based materials are omitted in this review).…”
Section: Introductionmentioning
confidence: 99%